The Interest of High School Students in Study Programs in College - Edy Karno (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the interest of students in high school in the study program at the university. This study uses a survey research approach. The research was conducted in Buton Regency. There were 292 participants taken from high school. Primary data was collected through questionnaires and secondary data was taken from the literature review. The data analysis technique used is the percentage technique and cross-tabulation. The results of the study found several majors that high school students were interested in if they wanted to continue their education in college. The majors are Information Technology, Accounting, Civil Engineering, Computers, Marine and Fisheries, Management, Development Economics, Forestry and Environment, Fisheries and Marine Affairs. The choice of majors reflects the choice of students according to the resources and needs of Buton Regency. Students know about job opportunities that have great opportunities to absorb labour. The results of the study also have implications for the understanding that universities wishing to develop and establish new study programs must be based on regional development needs